The joy of signing video companion to the book The joy of signing - Riekehof, Lottie L.; Holder, Eddie; Deaf Video Communications of America (Firm) (Carol Stream, IL : Deaf Video Communications of America, 2008)
Lottie Riekehof demonstrates the signs in the order in which they appear in her book of the same title. Eddie Holder provides a visual model by using mime, body language, and facial expressions to demonstrate the concept upon which the sign is based or to give cues to help remember the sign. Then the sign is used in context.
disc 1. Introduction ; Fingerspelling ; Family relationships ; Pronouns, question words, and endings ; Time ; Mental action ; Emotion and feeling -- disc 2. People, occupations, and money ; Physical movement and travel ; Opposites ; Location and direction ; Verbs and related words, part 1 -- disc 3. Verbs and related words, part 2 ; Quality, kind, and condition ; Quantity, size, and degree ; Communication and government ; Education -- Disc 4. Miscellaneous nouns ; Nature ; Body, medicine, and health ; Home, furniture, and clothing ; Foods and related words -- disc 5. Sports and recreation ; Countries, cities, and states ; Animals ; Religion ; Numbers.
DVD.
Title from container.
Originally issued on videocassette in 1981.
Keywords: American Sign Language; Sign language; Deaf people -- Means of communication